Safety of the hospitalized patient in Essalud - Rivera Tejada, Helen Soledad (2020)
Goals. To determine the effect of strategies for monitoring adverse events in the safety of the hospitalized patient in EsSalud, La Libertad, Trujillo. Material and method. Explanatory quantitative research. The sample was 47 nurses. A valid and reliable questionnaire on patient safety in hospitals modified by the authors was applied. Results. Both patient safety and strategies for monitoring adverse events were perceived by nurses at a medium level with 66% and 87.2% respectively. Conclusions. There is a moderate direct correlation between supervision strategies and patient safety (RS = 0.525; P <0.01). Likewise, the coefficient of determination was 27.5% as a positive effect. The results obtained will contribute to the satisfaction of the hospitalized patient and their relatives; while improving patient safety by reducing the occurrence of adverse events and promoting a culture of quality of care.